Advanced Education and Training Programs to Support Renewable Energy Investment in Africa - Kimuli, Daniel; Nabaterega, Resty; Banadda, Noble; Kabenge, Isa; Ekwamu, Adipala; Nampala, Paul (International Journal of Education and Practice, 2017)
African countries have initiated programs to generate electricity from renewable sources such as; wind, solar, biomass and hydropower. These initiatives are intended to reduce the carbon footprint of these countries in the wake of heavy dependency on fossil fuels and also provide cheap and accessible electricity to rural areas. These renewable energy programs are expected to deliver regional development and economic empowerment. However, the lack of trained manpower for repair and maintenance of renewable energy technologies devices is likely to result in failure of these technologies, cause losses in revenue and reduction in consumer faith in renewable energy technologies. African universities must be at the core of solving these challenges by training specialized professionals in renewable energy at graduate level and through short courses to meet the increasing demands for qualified human resource to support the sector. Thus to establish the “readiness” of Universities in Africa to offer advanced education and training in renewable energy, a review of all Masters Courses, Ph.D. programs and short courses was carried out. The results identified 21 English-language Masters courses, 3 providers of Ph.D. studies and 9 short courses in or with significant renewable energy content. Generally, there is inadequate advanced training in renewable energy especially at Ph.D. level in Africa thus the need to attract more African Universities to offer such programs at both masters and Ph.D. levels.
Keywords: African countries, Higher education, Masters and PhD training, Universities